2005
DOI: 10.1007/s10562-005-4902-6
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite NaY-supported gold complexes prepared from Au(CH3)2(C5H7O2): reactivity with carbon monoxide

Abstract: Mononuclear gold complexes in zeolite NaY were synthesized from initially physisorbed Au(CH 3 ) 2 (C 5 H 7 O 2 ), and their reactions with CO in a flow system at 298 K and 760 Torr were investigated by infrared (IR) spectroscopy and mass spectral analysis of the effluent gases. CH 4 and CO 2 were formed as CO flowed through the sample either steadily or as successive pulses. The results are consistent with the inferences that (a) CO reacted with the supported gold to form gold carbonyls, (b) CH 4 formed by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
(39 reference statements)
5
24
0
2
Order By: Relevance
“…This includes transfer of activated oxygen from the support (i.e., reducible or irreducible support), or special active sites at the metal/oxide boundary [8,[54][55][56][57][58][59][60][61][62][63][64]. Finally, there are a number of reports of catalysts consisting of single or a few Au + ions in the support [27,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. We note that combinations of the above effects can come into play; the gold-support interaction may for instance determine the morphology of the gold particles and thus influence the number of low-coordinated atoms or the strain.…”
Section: Introductionmentioning
confidence: 99%
“…This includes transfer of activated oxygen from the support (i.e., reducible or irreducible support), or special active sites at the metal/oxide boundary [8,[54][55][56][57][58][59][60][61][62][63][64]. Finally, there are a number of reports of catalysts consisting of single or a few Au + ions in the support [27,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. We note that combinations of the above effects can come into play; the gold-support interaction may for instance determine the morphology of the gold particles and thus influence the number of low-coordinated atoms or the strain.…”
Section: Introductionmentioning
confidence: 99%
“…Another important conclusion of the same study was that the type of CO stream can influence the change in the gold oxidation state: If CO is added in pulses, gold remained unreduced (Au III ), but in steadily flowing CO, the reduction of cationic gold (Au III ) to zero valent gold (Au 0 ) was observed. [45] In both cases, CO 2 was formed.…”
Section: Heterogenization Of Gold Catalystsmentioning
confidence: 92%
“…[ 45] In another work of Fierro-Gonzalez et al, [45] the NaY zeolite was also used and it was demonstrated that the initial CH 3 ligands from the CAu0 complex can be released during the reaction. Steadily flowing or pulsed CO reacted in the active Au site, which produces CO 2 and CH 4 , the latter probably being formed by the reaction of CH 3 groups, linked to the Au atom with H 2 O in the stream.…”
Section: Heterogenization Of Gold Catalystsmentioning
confidence: 99%
“…and catalysis since Haruta et al reported their remarkably high activity for low temperature CO oxidation [1]. Since this breakthrough, the reaction has been studied extensively, on supported particles [2][3][4][5], atomically dispersed species [6,7], and Surf. Sci.…”
Section: Introductionmentioning
confidence: 99%